Experimental and MD simulation study of surface residual stress and surface quality of SiCp/Al in pulsed laser-ultrasonic assisted grinding - Jieqiong Lin; Bin Fu; Yan Gu; Yuan Xi; Licheng Fu; Shuang Wu; Mingshuo Kang; Guangyu Liang (Journal of Materials Research and Technology, 2024)
The utilisation of aluminium-based silicon carbide composites (SiCp/Al) is on the rise. However, during the grinding process, where abrasive particles compel SiC particles into the aluminium matrix, stress concentration occurs near the interface between the two phases. This phenomenon results in adverse surface deformation accompanied by residual compressive stress (RCS). Consequently, a pulsed laser-ultrasonic-assisted grinding method (PL-UAG) has been proposed. The effectiveness of the method is verified through grinding experiments. Moreover, the influence process of the thermal effect of pulsed laser and the evolution mechanism of microscopic RS near the SiCp/Al two-phase interface are revealed through molecular dynamics simulation. The experimental results show that the surface RCS of SiCp/Al gradually decreases and transforms into residual tensile stress (RTS) with the increase of laser power. The RCS increases with the grinding depth. The RCS is reduced to 17 Mpa and the surface roughness Sa value is reduced to 0.110 μm with the laser power is 40 W and the grinding depth is 1 μm. The simulation results show that the energy dissipation process of pulsed laser helps to reduce thermal deformation and damage. The laser-induced thermal effect reduces the deformation of the aluminium matrix caused by particle extrusion and inhibits the formation and slip of dislocations in the aluminium matrix. In addition, the ultrasonic shock effect effectively weakens the RTS generated by the laser.